2009
DOI: 10.1016/j.ydbio.2009.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid receptors are required for skeletal growth, matrix homeostasis and growth plate function in postnatal mouse

Abstract: The retinoic acid receptors α, β and γ (RARα, RARβ and RARγ) are nuclear hormone receptors that regulate fundamental processes during embryogenesis, but their roles in skeletal development and growth remain unclear. To study skeletal-specific RAR function, we created conditional mouse mutants deficient in RAR expression in cartilage. We find that mice deficient in RARα and RARγ (or RARβ and RARγ) exhibit severe growth retardation obvious by about 3 weeks postnatally. Their growth plates are defective and, impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
100
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(107 citation statements)
references
References 78 publications
7
100
0
Order By: Relevance
“…PTHrP regulates the expression of Ihh, which controls chondrocyte proliferation and maturation, and Ihh in turn regulates Pthrp expression, creating a feedback system that controls the growth of skeletal elements (Kronenberg, 2006). The hypertrophic portions of the growth plate have been shown to contain higher levels of endogenous retinoid signalling than the upper, immature zones and a requirement for RAR-mediated repression in the upper growth plate zone has been shown to maintain chondrocyte function and the production of cartilageassociated extracellular matrix proteins (Williams et al, 2010;Williams et al, 2009). Previous studies have also suggested that RA-mediated repression of target gene expression in the upper zone is necessary to maintain physiological levels of Ihh expression (Koyama et al, 1999).…”
Section: Ra and Chondrocyte Hypertrophymentioning
confidence: 99%
See 1 more Smart Citation
“…PTHrP regulates the expression of Ihh, which controls chondrocyte proliferation and maturation, and Ihh in turn regulates Pthrp expression, creating a feedback system that controls the growth of skeletal elements (Kronenberg, 2006). The hypertrophic portions of the growth plate have been shown to contain higher levels of endogenous retinoid signalling than the upper, immature zones and a requirement for RAR-mediated repression in the upper growth plate zone has been shown to maintain chondrocyte function and the production of cartilageassociated extracellular matrix proteins (Williams et al, 2010;Williams et al, 2009). Previous studies have also suggested that RA-mediated repression of target gene expression in the upper zone is necessary to maintain physiological levels of Ihh expression (Koyama et al, 1999).…”
Section: Ra and Chondrocyte Hypertrophymentioning
confidence: 99%
“…In the skeleton, deletion of both Rara and Rarg leads to widespread defects (underossification, loss and gain of bones) in the axial and appendicular skeleton and cranium Mendelsohn et al, 1994). More recently, analysis of Rara,Rarg and Rarb,Rarg double knockouts has shown that RAR-mediated repression is essential for growth plate function and cartilage matrix homeostasis (Williams et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…RAR/RXR complexes work as transcriptional repressors with no ligand and as activators in the presence of RA ligand (Rochette-Egly and Germain, 2009). Limiting RA concentration, inhibiting RAR signaling, or inhibiting RA metabolism has detrimental effects on limb development in chicks (Roselló-Díez et al, 2011;Stratford et al, 1996), zebrafish (Grandel et al, 2002) and mammals (Dranse et al, 2011;Lohnes et al, 1994;Niederreither et al, 2002;Sandell et al, 2012Sandell et al, , 2007Williams et al, 2009;Yashiro et al, 2004). The role of RA during limb regeneration is less clear (Blum and Begemann, 2013), although several lines of evidence support an active role.…”
Section: Introductionmentioning
confidence: 99%
“…Retinoic acid (RA) has been shown to play multiple roles in bone development and repair by exerting pleiotropic effects on cells of the chondroblast, osteoblast and osteoclast lineages (Adams et al, 2007;Allen et al, 2002;Conaway et al, 2013;Dranse et al, 2011;Koyama et al, 1999;Laue et al, 2008Laue et al, , 2011Li et al, 2010;Lie and Moren, 2012;Lind et al, 2013;Nallamshetty et al, 2013;Song et al, 2005;Spoorendonk et al, 2008;Weston et al, 2003;Williams et al, 2009). Although partially conflicting results were reported, the general consensus for osteoblastogenesis is that RA signaling restricts osteoblast differentiation but promotes subsequent bone matrix synthesis by mature osteoblasts.…”
Section: Introductionmentioning
confidence: 99%